2016
DOI: 10.1016/j.neuro.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal T1 relaxation rate (R1) captures changes in short-term Mn exposure in welders

Abstract: Objectives We demonstrated recently that the T1 relaxation rate (R1) captured short-term Mn exposure in welders with chronic, relatively low exposure levels in a cross-sectional study. In the current study, we used a longitudinal design to examine whether R1 values reflect the short-term dynamics of Mn exposure. Methods Twenty-nine welders were evaluated at baseline and 12 months. Occupational questionnaires estimated short-term welding exposure using welding hours in the 90 days prior to each study visit (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In contrast, we designed a screening tool that could be administered consistently by an ancillary staff person in a physician’s office. Nevertheless, we modeled our proposed manganism screening on their tiered-screening protocol and recommend that workers identified undergo magnetic resonance imaging (MRI) of the brain to measure T1 relaxation time(Lee et al, 2015; Lewis et al, 2016) or pallidal index. (Criswell et al, 2012; Nelson et al, 1993) We recommend that those workers identified as having parkinsonism and who have a shortened T1 relaxation time or high pallidal index, should have an evaluation by a neurologist, preferably one with movement disorders training, in order to confirm clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we designed a screening tool that could be administered consistently by an ancillary staff person in a physician’s office. Nevertheless, we modeled our proposed manganism screening on their tiered-screening protocol and recommend that workers identified undergo magnetic resonance imaging (MRI) of the brain to measure T1 relaxation time(Lee et al, 2015; Lewis et al, 2016) or pallidal index. (Criswell et al, 2012; Nelson et al, 1993) We recommend that those workers identified as having parkinsonism and who have a shortened T1 relaxation time or high pallidal index, should have an evaluation by a neurologist, preferably one with movement disorders training, in order to confirm clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…A one-year follow-up analysis was conducted on this cohort that demonstrated changes in R1 values in all ROIs correlated with changes in HrsW 90 (the short-term welding exposure metric), whereas blood Mn levels or the PI value failed to show any associations with changes in HrsW 90 (Lewis et al, 2016a). This result is consistent with a previous finding that the GP T1 relaxation time (1/R1) in Mn-exposed monkeys was lowest after 120 days of Mn-exposure, but returned to control values two months after cessation of Mn-exposure, suggesting that R1 may sensitively capture the temporal dynamics of Mn brain accumulation and clearance (Han et al, 2008).…”
Section: R1 (1/t1) Signals Capture Non-linear Short-term Mn Accumulamentioning
confidence: 95%
“…Indeed, X-ray fluorescence imaging has shown accumulation of Mn in the globus pallidus (GP), thalamus and substantia nigra pars compacta (Robison et al, 2012;Robison et al, 2015). Chronic Mn exposure affects the GP via the production of a large number of free radicals that interfere with neurotransmitter metabolism and ultimately lead to neuronal damage (Avila et al, 2008;Lewis et al, 2016). Mn also accumulates in the hippocampal formation, as revealed by magnetic resonance imaging (Robison et al, 2013).…”
Section: Introductionmentioning
confidence: 99%